INVENTARISASI TANAM TUMBUH DAN POLA RUANG PADA TAPAK TOWER SALURAN UDARA TEGANGAN TINGGI 150 KV AMUNTAI-TAMIANG LAYANG - Aipansyah -; Suyanto -; Eko Rini Indrayatie (Universitas Lambung Mangkurat, 2021)
Forest inventory is an activity to determine forest potential which is adjusted to the objectives to be achieved. Forest inventorying activities in other fields such as electricity are known as plant inventories with economic value. The use of electricity is an important factor in people's lives, both in the household sector, lighting, communication, industry and so on. The Government's program, which targets an additional 56.4 thousand megawatts of electricity in the next 10 years, requires a large number of high-voltage air duct. Purpose of this research is to produce data on the types and potential of economic plants on the Amutai-Tamiang Layang HVAD tower site. The method in this research is a 100% census of 120 tower site points, covering three regencies namely Hulu Sungai Utara Regency, Tabalong Regency, and East Barito Regency. The results of this research were 41 species of plants with the potential for plants which were found to be small and unproductive plants as many as 32 plant species and 1979 stems, while the potential for productive plants was 11 species with the number 1076 stems and potential for large plants totaling 25 species with a total of 416 stems. The research location of 120 points is included in the spatial pattern of other use areas so that PT PLN (Persero) no longer carries out a business license for utilization of wood forest products (IUPHHK) to the Ministry of Forestry and the Environment.Keywords: Plants Inventory; Tower Site; HVAD.